Visual Recovery after Primary Retinal Detachment Surgery: Biofeedback Rehabilitative Strategy - Enzo M. Vingolo; Serena Fragiotta; Daniela Domanico; Paolo G. Limoli; Marcella Nebbioso; Leopoldo Spadea (Journal of Ophthalmology)
Purpose. To evaluate possible speeding up recovery time after retinal detachment (RD) surgery using biofeedback strategy. Methods. A total of 52 eyes were selected. After surgery, patients were divided into two groups: group A, including patients submitted to biofeedback with MP-1 strategy; group B, patients who received common care strategy. Biofeedback strategy was started 15 days after the suspension of cycloplegic eye drops in buckling procedure or after silicone oil removal in the vitrectomized eyes. Controls were scheduled at baseline and 6, 12, and 18 weeks. Results. At baseline, there was no significant difference in BCVA between groups (P=0.4230). At the end of biofeedback treatment (WK 6) BCVA of group A was significantly better (P<0.001) than group B and BCVA was still better in group A than group B at WK 12 (P=0.028) and at WK 18 (P=0.041). Conclusions. Visual recovery after RD surgery is still unclear, and it does not depend on entity of the RD. Our data demonstrate that in biofeedback group there was a significant recovery in visual performances that still remains evident after 3 months from the baseline.